Faktor-Faktor Risiko Rabies pada Anjing di Bali (RISK FACTORS ANALYSIS FOR RABIES INDOGS IN BALI) - Dibia, I Nyoman; Sumiarto, Bambang; Susetya, Heru; Putra, Anak Agung Gde; Scott-Orr, Helen (Jurnal Veteriner, 2015)
The efforts to eradicate rabies in Bali have been done for more than three years. However, therabiescases is still spreading. Thus, rabies virus continues to infect humans. A case-control study wasconducted to identify the risk factors associated with rabid dog in Bali. Cases were defined as dogsconfirmed having rabies by direct fluorescent antibody test (dFAT). Determination of sample amount ineach district was taken proportionally and samples were taken by using simple random sampling. A totalof 51 rabid dog cases between 2010 and 2011 and 102 uninfected rabies dogs as control were used in thisstudy. Possible associated factors were obtained by doing questionnaire. The data were subsequentlyanalyzed using chi-square (X2) and odds-ratio (OR) for possible association, which were ultimately analyzedby means of logistic regression to build up of model. This study revealed that factors associated with rabiddog were the status of rabies vaccination (X2= 55.538; P= 0.000; OR= 19.133; 95% CI= 8.015<OR<45.678),contact with other dog (X2= 43.659; P= 0.000; OR= 12.551; 95% CI= 5.541<OR<28.430),condition of dog(X2= 9.994; P= 0.002; OR= 3.019; 95% CI= 1.504<OR<6.058),number of raised dog (X2= 9.284; P= 0.002;OR= 2.962; 95% CI= 1.455<OR<6.027), and veterinary care (X2= 5.258; P= 0.022; OR= 2.444; 95% CI=1.125<OR<5.310). It was found an appropriate logit model to estimate probability of rabid dog events inBali province as follows : Logit Pr (rabies=1| x) = - 4.413 + 3.919 (status of rabies vaccination) + 3.457(contact with other dog). This study is expected to be used as a reference in order to improve rabies controleffectiveness in Bali.
Keywords: rabid dog, risk factors, case-control study of rabies